2012
DOI: 10.1136/heartjnl-2012-302531
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of myocardial CT perfusion in patients presenting with acute chest pain to the emergency department: comparison with SPECT-myocardial perfusion imaging

Abstract: In patients presenting to the ED with CP, the evaluation of rest myocardial CTP demonstrates high diagnostic performance as compared with SPECT-MPI. Addition of CTP to CTA improves the accuracy of CTA, primarily by reducing rates of false-positive CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 40 publications
2
17
1
Order By: Relevance
“…The presence of a myocardial hypo-enhancement region at rest on CCT has a sensitivity and specificity of around 90% to identify patients with a MI (Figures 5-7) (89,90). Rest dual energy CT provided comprehensive CAD imaging and identified perfusion defects in 90% of cases compared to SPECT (60).…”
Section: A B and The Assessment Of MI Ischemia And Viability (88)mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a myocardial hypo-enhancement region at rest on CCT has a sensitivity and specificity of around 90% to identify patients with a MI (Figures 5-7) (89,90). Rest dual energy CT provided comprehensive CAD imaging and identified perfusion defects in 90% of cases compared to SPECT (60).…”
Section: A B and The Assessment Of MI Ischemia And Viability (88)mentioning
confidence: 99%
“…Authors retrospectively evaluated fifty-three patients who underwent stress dynamic CTP and either SPECT (n = 25) or CMR (n = 28) and found that for detecting the abnormal perfused myocardium, sensitivity and specificity were 80% (95% CI, 71-90) and 86% (95% CI, 76-91) in SPECT (cut-off MBF, 1.23), and 82% (95% CI, 76-88) and 87% (95% CI, [80][81][82][83][84][85][86][87][88][89][90][91][92] in CMR (cut-off MBF, 1.25) (69).…”
Section: A B and The Assessment Of MI Ischemia And Viability (88)mentioning
confidence: 99%
“…100 A first evidence of CT perfusion applied in the evaluation of patients with ACP (TIMI risk score ,4) presenting at the ED has demonstrated that rest CT perfusion was highly accurate in the detection of perfusion defects, with a sensitivity of 92% and specificity of 95% as compared with SPECT. 101 Adding CT perfusion information to the cardiac CT data resulted in better PPV with reduced rates of false positives ( Figure 5). 101 Accordingly, in a subanalysis of the ROMICAT I trial, the sensitivity for ACS increased from 77% for obstructive CAD to 90% with addition of rest CT perfusion.…”
Section: Plaque Features Associated With Vulnerabilitymentioning
confidence: 99%
“…101 Adding CT perfusion information to the cardiac CT data resulted in better PPV with reduced rates of false positives ( Figure 5). 101 Accordingly, in a subanalysis of the ROMICAT I trial, the sensitivity for ACS increased from 77% for obstructive CAD to 90% with addition of rest CT perfusion. 102 Finally, a first recent prognostic study in a large cohort of patients (nearly 400 patients) showed that the extent and severity of rest myocardial hypoperfusion in addition to signs of necrotic myocardium as detected by CT prior to invasive coronary evaluation and revascularization is significantly and independently related to long-term (median 50 months) outcome in patients with NSTEMI.…”
Section: Plaque Features Associated With Vulnerabilitymentioning
confidence: 99%
“…Most of the studies to date were performed with wide-detector MDCT or DSCT for higher temporal resolution that is preferred for CTP studies; however, single-source 64-detector MDCT has shown to be feasible as well. 32,33 DECT technology also has been used for CTP to improve depiction power of perfusion defects by assessing changes in iodine distribution within the myocardium. 34 In CCTA images, ischemic and nonviable myocardium is expressed as a hypoattenuation area reflecting diminished content of contrast medium within that particular myocardium -also known as myocardial blood pool defect.…”
Section: Computed Tomography Perfusionmentioning
confidence: 99%